2024
DOI: 10.1002/1873-3468.14811
|View full text |Cite
|
Sign up to set email alerts
|

The prefoldin‐like protein AtURI exhibits characteristics of intrinsically disordered proteins

Yaiza Gómez‐Mínguez,
Alberto Palacios‐Abella,
Cecilia Costigliolo‐Rojas
et al.

Abstract: The prefoldin‐like protein UNCONVENTIONAL PREFOLDIN RPB5 INTERACTOR (URI) participates in diverse cellular functions, including protein homeostasis, transcription, translation, and signal transduction. Thus, URI is a highly versatile protein, although the molecular basis of this versatility remains unknown. In this work, we show that Arabidopsis thaliana (Arabidopsis) URI (AtURI) possesses a large intrinsically disordered region (IDR) spanning most of the C‐terminal part of the protein, a feature conserved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Very recent studies in Arabidopsis indicates the existence of PFDL subunits in plants [ 26 , 32 ]. Arabidopsis URI ortholog was firstly identified by forward genetic screening with altered auxin distribution [ 32 ].…”
Section: Structure Of the Prefoldin Complex And Prefoldin-like Complexmentioning
confidence: 99%
See 4 more Smart Citations
“…Very recent studies in Arabidopsis indicates the existence of PFDL subunits in plants [ 26 , 32 ]. Arabidopsis URI ortholog was firstly identified by forward genetic screening with altered auxin distribution [ 32 ].…”
Section: Structure Of the Prefoldin Complex And Prefoldin-like Complexmentioning
confidence: 99%
“…Arabidopsis URI ortholog was firstly identified by forward genetic screening with altered auxin distribution [ 32 ]. Further analysis demonstrated that URI was the PFDL subunits and showed conserved roles in Arabidopsis [ 26 , 32 ]. Moreover, putative ortholog analysis identified PDRG1 , UXT , and ASDURF genes ( Table 1 ), and AP-MS assay demonstrated URI, PFD2, PFD6, PDRG1, and ASDURF as interactors of UXT [ 26 ].…”
Section: Structure Of the Prefoldin Complex And Prefoldin-like Complexmentioning
confidence: 99%
See 3 more Smart Citations